(untitled) (Journal of Geography and Environmental Management, 2022)
To conduct quantitative and qualitative assessment of activities in the catchment areas of river basins using a variety of principles and methods, multi-year systematic objectively hydrological, hydrogeochemical and economic information and analytical materials are needed. At the same time, the scientific and theoretical value of surface water quality assessment of river basins is determined to some extent by the mathematical correctness of the tasks and methods of their solutions, which characterize the validity and reliability of hydrogeochemical processes of watershed areas of river basins, which dictates the need for structural analysis of complex hydrochemical indexes of surface water pollution assessment, based on natural laws, principles and properties of natural processes. The aim of the study is to develop mathematical models based on the genetic theory of hydrochemical processes of the natural system to assess activities in the watershed territories of river basins. In this paper developed mathematical models to improve the tools to assess the quality of surface waters of river basin catchments, based on the solution of differential equations of hydrochemical processes of natural systems, corresponding to the physical and mathematical sign of the practical problems of hydrochemistry and the principles of non-linearity of natural processes, are the result of using classical mathematical methods of modelling and their analytical analysis The proposed approach to the assessment of surface water quality in the catchment area of river basins in conjunction with geographical analysis can be used for comprehensive geo-ecological studies to develop recommendations for the rational management of water resources under anthropogenic activities.